Fecal Microbiota of Toxigenic Clostridioides difficile-Associated Diarrhea - Hernández, Marta; de Frutos, Mónica; Rodríguez-Lázaro, David; López-Urrutia, Luis; Quijada, Narciso M.; Eiros, Jose María (Frontiers in Microbiology, 2019)
Clostridioides difficile infection (CDI) is currently one of the most important causes of infectious diarrhea in developed countries and the main cause in healthcare settings. Here, we characterized the gut microbiota from the feces of 57 patients with diarrhea from nosocomial and community-acquired CDI. We performed an ecological analysis by high-throughput sequencing of the V3-V4 region of 16S rRNA amplicons and evaluated the association of the various ecological profiles with CDI risk factors. Among all samples Bacteroidaceae 31.01%, Enterobacteriaceae 9,82%, Lachnospiraceae 9,33%, Tannerellaceae 6,16%, and Ruminococcaceae 5,64%, were the most abundant families. A reduced abundance of Bacteroides was associated with a poor CDI prognosis, with severe diarrhea and a high incidence of recurrence. This reduction was associated with a weakened host immune system and previous aggressive antibiotherapy. Peptostreptococcaceae family was 1.56% overall and within the family the only identified member was the genus Clostridioides, positively correlated with the presence of Akkermansia that may be predictive of the presence of a CDI. Finally, a relevant aspect that must be considered in clinical practice is the misdiagnosis of CDI, as patients with a stool sample that tests positive for C. difficile are usually diagnosed with CDI and subsequently treated as such. However, co-infection with other pathogenic agents often plays an important role in the development of diarrhea, and must be considered when prescribing antibiotic treatment.